Compstatin : a C3-targeted complement inhibitor reaching its prime for bedside intervention - Mastellos, Dimitrios C; Yancopoulou, Despina; Kokkinos, Petros; Huber-Lang, Markus; Hajishengallis, George; Biglarnia, Ali R ; 0009-0004-2293-0740; Lupu, Florea; Nilsson, Bo; Risitano, Antonio M; Ricklin, Daniel; Lambris, John D (European Journal of Clinical Investigation, 2015)
There is a growing awareness that complement plays an integral role in human physiology and disease, transcending its traditional perception as an accessory system for pathogen clearance and opsonic cell killing. As the list of pathologies linked to dysregulated complement activation grows longer, it has become clear that targeted modulation of this innate immune system opens new windows of therapeutic opportunity for anti-inflammatory drug design. Indeed, the introduction of the first complement-targeting drugs has reignited a vibrant interest in the clinical translation of complement-based inhibitors. Compstatin was discovered as a cyclic peptide that inhibits complement activation by binding C3 and interfering with convertase formation and C3 cleavage. As the convergence point of all activation pathways and a molecular hub for crosstalk with multiple pathogenic pathways, C3 represents an attractive target for therapeutic modulation of the complement cascade. A multidisciplinary drug optimization effort encompassing rational 'wet' and in silico synthetic approaches and an array of biophysical, structural and analytical tools has culminated in an impressive structure-function refinement of compstatin, yielding a series of analogues that show promise for a wide spectrum of clinical applications. These new derivatives have improved inhibitory potency and pharmacokinetic profiles and show efficacy in clinically relevant primate models of disease. This review provides an up-to-date survey of the drug design effort placed on the compstatin family of C3 inhibitors, highlighting the most promising drug candidates. It also discusses translational challenges in complement drug discovery and peptide drug development and reviews concerns related to systemic C3 interception.
© 2015 Stichting European Society for Clinical Investigation Journal Foundation.
Keywords: Animals; Complement C3/antagonists & inhibitors; Complement Inactivating Agents; Drug Design; Drug Discovery; Humans; Peptides; Peptides, Cyclic